Factor Influencing to Quality of Life among Elderly Living in Community at Nonthaburi Province - Santwanpas, Nichada; Adunwatanasiri, Patoomthip; Sindhu, Siriorn (Journal of The Royal Thai Army Nurses, 2024)
This research aimed to analyze the factors that influenced of quality of life among elderly who lived in the community of Nonthaburi province. Participants were 116 elderly aged 60 and above. The data collection instrument was a questionnaire composed of 4 parts: 1) Demographic data and access to healthcare services, 2) Health literacy (HLS-EU-Q16), 3) Frailty (the Tilburg Frailty Indicator), and 4) Quality of life (WHOQOL-AGE). The reliability coefficients of parts 2 and 4 were 0.84 and 0.98 respectively, and the Tilburg Frailty Indicator questionnaire finds KR-20 equal to 0.95. Descriptive statistics and stepwise multiple regression analysis were used in data analysis with a statistical significance at the level of .05 The research findings revealed that the elderly had a moderate quality of life at 60.34% (mean ± SD = 40.16 ± 10.46). Income sufficiency ( = 0.49, p = 0.000), activities of daily living (Barthel index) ( = 0.19, p = 0.003), high health literacy score ( = 0.17, p = 0.042), and the number of nurse home visits per year ( = 0.16, p = 0.028) could be explained the quality of life 57.6% of the variance (R2 = 0.576). Therefore, policymakers should promote an active aging society in communities and create sufficient income opportunities for the elderly to adequately manage health problems, reduce dependency, and nurse home visits are crucial in promoting a good quality of life for the elderly.